Constitutive expression of StAATP, a potato plastidic ATP/ADP transporter gene, increases starch content in transgenic Arabidopsis. Issue 2 (4th March 2017) - Wang, Feibing; Fu, Lifeng; Kong, Weili; Ye, Yuxiu; Chen, Xinhong; Zhou, Qin; Chen, Boqing
ABSTRACT: The plastidic ATP/ADP transporter (AATP) imports adenosine triphosphate (ATP) from the cytosol into plastids, resulting in an increase in the ATP supply to facilitate the anabolic synthesis in heterotrophic plastids of dicotyledonous plants. In this study, a gene encoding the AATP protein, StAATP, was successfully isolated from potato and transformed into Arabidopsis . Constitutive expression of StAATP significantly increased the starch accumulation in the transgenic plants. Real-time quantitative polymerase chain reaction analysis showed that constitutive expression of StAATP up-regulated the expression of key genes involved in the starch biosynthesis pathway in the transgenic Arabidopsis plants: phosphoglucomutase ( AtPGM ), ADP-glucose pyrophosphorylase (AGPase) small subunit ( AtAGPase-S1 and AtAGPase-S2 ), AGPase large subunit ( AtAGPase-L1 and AtAGPase-L2 ), granule-bound starch synthase ( AtGBSS I and AtGBSS II ), soluble starch synthases ( AtSSS I, AtSSS II, AtSSS III and AtSSS IV ) and starch-branching enzyme ( AtSBE I and AtSBE II ) genes. Furthermore, the major enzymes involved in starch biosynthesis (AGPase, GBSS, SSS and SBE) exhibited higher catalytic activities in the transgenic plants compared to the wild type. These results indicate that StAATP may improve the starch content of Arabidopsis by up-regulating the expression of the related genes and increasing the activities of the major enzymes involved in starch biosynthesis. All these findings suggest that the StAATP gene may be applied for increasing starch accumulation of plants in the future.